Polmas Gastronomy: The Transformation of Street Vendors Towards a Participatory Community Security System in Indonesia - Putra, Madiya Mawlana; Simanjuntak, Raja Luat; Bhiswara, Priya Kuntha; Faidzin, Syahrul; Dicky, Febrian (Proceedings of Police Academy, 2025)
As public trust in conventional policing models continues to swirl downward, this study builds on Indonesia's unique street food culture and the establishment of Gastronomy “Polmas” (Police and Community) - a community security framework that activates street food vendors as organic intelligence agents. This study will look at the "Rantang Aman" program in Surakarta, Indonesia as: (1)a formative culinary ecosystem of security; (2) the effectiveness of intelligence encrypted in food; and (3) a community model that is replicable. Using mixed methods (participatory action research with 120 vendors, social network analysis, quasi-experiment, and digital ethnography), results demonstrated a 31% reduction in street crime, emergency response acceleration from 60 to 12 minutes, 22% increased vendor revenue, and surged community trust (38% to 82%). Hybrid analog-digital tools (e.g., "kentongan digital") proved vital for connectivity gaps. We conclude that culinary codes and vendor networks create high-efficiency security infrastructures, outperforming conventional surveillance while boosting local economies. Implications include policy integration into national Polmas guidelines, "gerobak smart" subsidies for scalability, and a transferable Global South blueprint where street food ecosystems convert informal economies into security assets – proving security can be collaboratively "cooked" in community woks.